Gambling and Consumption - Riitta Matilainen (Suomen Antropologi, 2011)
Gambling is a consumption decision (e.g., Garvía 2007: 644; Casey 2008). Sociologist Emma Casey (2008: 3), who has studied British working-class women’s  xperiences of the National lottery, points out that buying a lottery ticket is a very popular routine purchase with unique mass appeal. Nonetheless, gambling can still have a rather dubious image. Sociologist Colin Campbell (1998: 235, 238) describes the tendency of intellectual discussions of consumption to use a dichotomy of need and want. The former is viewed as ‘a legitimate activity’, because it satisfies what is necessary, whereas catering to ‘non-essential’ or ‘superficial’ desires is seen to be driven by ‘ethically dubious motives’. The rhetoric of need has therefore dominated the study of consumption as well as the views of ordinary people. As gambling falls into the ‘want’ category it has had the unfortunate fate of having been regarded as something unnecessary and objectionable.